From research to practice: Adapting agriculture to climate today for tomorrow in Ethiopia - Grossi, Amanda; Dinku, Tufa (Frontiers in Climate, 2022)
Eighty percent of the world's agriculture is rainfed, making it highly vulnerable to climate fluctuations and stresses, such as those brought about by climate variability and change. Sub-Saharan Africa and Ethiopia in particular have experienced a significant increase in climate variability over the past decade, which has led to more frequent weather extremes such as floods and droughts. Because 85% of Ethiopia depends upon agriculture for its livelihoods, such rainfall shortages or excesses can impede food production, access to financial and natural assets, and the ability to recover in subsequent crop seasons. This means that climate variability in agriculture not only affects the availability of the food Ethiopians consume, but also the income of its smallholder farmers. Variability in rainfall and temperature can also have adverse effects on livestock and the pastoralists whose livelihoods depend upon it. Thus, all development planning and practice in the agriculture and related sectors need to take climate variability and long-term climate change into account. Climate services can contribute to the alleviation of a range of climate-sensitive development challenges, including agricultural production and food security. The Adapting Agriculture to Climate Today for Tomorrow (ACToday) approach of the International Research Institute for Climate and Society (IRI), Columbia University, USA, aims to develop climate service solutions through enhancement of the availability and effectiveness of climate information in national policy, planning, management, and other decision-making processes in countries that are particularly dependent on agriculture and vulnerable to the effects of climate variability and change. It targets improved food security, nutrition, environmental sustainability and economic outcomes in these countries by promoting the use of climate information and services to manage current climate risks, while laying the foundation for adaptation to future climatic conditions. In this Perspective, we share experiences from the implementation of the ACToday project and approach in Ethiopia, outlining its accomplishments and challenges. In doing so, we characterize best practices and pitfalls to avoid to ensure climate knowledge and information truly meet the needs of climate-informed decision making and climate-smart policy and planning. We also outline pragmatic guidance to ensure activities designed to evolve climate research into services are done so appropriately, responsibly, and sustainably to bridge the gap between those who produce climate information and those who ultimately use it.